Accuracy of self-reported weight in the Women's Health Initiative. Issue 6 (19th November 2018) - Luo, Juhua; Thomson, Cynthia A; Hendryx, Michael; Tinker, Lesley F; Manson, JoAnn E; Li, Yueyao; Nelson, Dorothy A; Vitolins, Mara Z; Seguin, Rebecca A; Eaton, Charles B; Wactawski-Wende, Jean; Margolis, Karen L
Abstract: Objective: To assess the extent of error present in self-reported weight data in the Women's Health Initiative, variables that may be associated with error, and to develop methods to reduce any identified error. Design: Prospective cohort study. Setting: Forty clinical centres in the USA. Participants: Women ( n 75 336) participating in the Women's Health Initiative Observational Study (WHI-OS) and women ( n 6236) participating in the WHI Long Life Study (LLS) with self-reported and measured weight collected about 20 years later (2013–2014). Results: The correlation between self-reported and measured weights was 0·97. On average, women under-reported their weight by about 2 lb (0·91 kg). The discrepancies varied by age, race/ethnicity, education and BMI. Compared with normal-weight women, underweight women over-reported their weight by 3·86 lb (1·75 kg) and obese women under-reported their weight by 4·18 lb (1·90 kg) on average. The higher the degree of excess weight, the greater the under-reporting of weight. Adjusting self-reported weight for an individual's age, race/ethnicity and education yielded an identical average weight to that measured. Conclusions: Correlations between self-reported and measured weights in the WHI are high. Discrepancies varied by different sociodemographic characteristics, especially an individual's BMI. Correction of self-reported weight for individual characteristics could improve the accuracy of assessment of obesity status in postmenopausal women.